Analisis Narasi Visual dan Brand Image NCT 127 Dalam Promosi Album ‘Walk’ Di Instagram - Ni Made Eni Dwi Ayuni; I Gusti Ayu Agung Dewi Sucitawathi Pinatih; Ni Made Prasiwi Bestari; Jonathan Jacob Paul Latupeirissa (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This research aims to analyze the digital communication strategy of the @nct127 Instagram account in building a brand image through the promotion of the ‘Walk’ album. The study employs a qualitative descriptive method with a literature study approach, observing visual and narrative elements on social media. The results indicate that the promotion of the ‘Walk’ album successfully constructs a "Neo Culture" brand image through a multimodal communication approach that integrates persuasive copywriting, urban-street aesthetics, and interactive audio-visual synchronization. The use of Instagram Reels as a digital narrative engine significantly increased audience engagement and established a consistent visual identity. In conclusion, the orchestration of high-quality visual narratives and interactive features is the key factor in maintaining NCT 127's position as a trendsetter in the global music industry.